STRATEGI PEMBERDAYAAN EKONOMI SANTRI MELALUI PENGELOLAAN TOSERBA DI PONDOK PESANTREN SUNAN DRAJAT - Ahmad Nafi’ul Umam; Rahmat Agus Santosoi; Abdul Kholid Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the strategy of student empowerment in the economic sector through the Toko Serba Ada (TOSERBA) business unit at Sunan Drajat Islamic Boarding School. The focus includes the concept of student empowerment, the strategies implemented, and the implications of Islamic values in the empowerment process. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. Data analysis techniques include data condensation, data display, and conclusion drawing. The results show that student empowerment is carried out through stages of awareness, capacity building, and empowerment. The strategies applied include planning, organizing, actuating, and controlling by involving students directly in TOSERBA operations and providing competency-based training. Supporting factors include the leadership of the kyai, discipline values, and facility support, while constraints include limited professional human resources. Islamic values such as trustworthiness, justice, and cooperation serve as the foundation for developing students’ independence and entrepreneurial spirit